Evaluating strategies and outcomes following rotator cuff tears. (May 2019) - Amoo-Achampong, Kelms; Krill, Michael K; Acheampong, Derrick; Nwachukwu, Benedict U; McCormick, Frank
Introduction: Rotator cuff tear surgical repair techniques have significantly progressed. However, tendon retear following primary repair persistently occurs at high rates. Rehabilitation protocols, surgical fixation techniques, biologic therapy with scaffolds, platelet-rich plasma, and even stem cell applications are under study to promote adequate tendon healing. Methods: A nonsystematic query of the PubMed database was conducted in July 2016 utilizing the search terms "rotator cuff repair, " "tear, " "rehabilitation, " "scaffold, " "platelet-rich plasma, " and "stem cell" to identify, analyze, and summarize relevant studies. Conclusion: Individualized rehabilitation protocols may be the best approach for small to medium sized tears. Surgical fixation will continue to be debated as modifications to single-row technique and increases in suture number have improved tensile strength. Double-row repairs have been associated with higher costs. Transosseous equivalent technique exhibits comparable subjective and objective outcomes to single- and double-row repair at two-year follow-up. Biocompatible scaffold augmentation has showed inconsistent short-term results. Platelet-rich plasma has lacked uniformity in treatment preparation, administration, and outcome measurement with mixed results. Few human studies have suggested decreased retear rates and improved repair maintenance following bone marrow-derived mesenchymal stem cell augmentation. This review reiterated the necessity of additional high-quality, large-sample studies to develop any final verdict regarding efficacy.